2018
DOI: 10.1016/j.colegn.2017.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Living with multiple losses: Insights from patients living with pressure injury

Abstract: Background: Pressure injury is a common problem. Its prevention and treatment is predominantly focussed on views, perceptions and knowledge of healthcare staff rather than on patient experience, particularly those patients living in their own homes.Aim: This paper reports findings on patients experiences and perceptions of loss associated with PI.These findings are drawn from a larger study of pressure injury patients living and receiving care in the community.Methods: Qualitative interviews with 12 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 34 publications
0
58
0
5
Order By: Relevance
“…The 42 articles included in this review present results of 40 studies and were published between 1986 and 2019 (Table 1). Of these, 24 were qualitative studies 25,30‐32,50‐69 . Of the quantitative studies, 13 were cross‐sectional 70‐82 (of which six had a comparative approach, eg, ulcer vs non‐ulcer participants) and two were cohort studies 83,84 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 42 articles included in this review present results of 40 studies and were published between 1986 and 2019 (Table 1). Of these, 24 were qualitative studies 25,30‐32,50‐69 . Of the quantitative studies, 13 were cross‐sectional 70‐82 (of which six had a comparative approach, eg, ulcer vs non‐ulcer participants) and two were cohort studies 83,84 .…”
Section: Resultsmentioning
confidence: 99%
“…Beyond that, social participation not only influences health, but the health status also influences social participation 27,28 . Accordingly, experiencing pain, having limited mobility, or feeling shame because of wound odour and wound exudate leads to patients' rejection or inability to socially participate 29‐32 …”
Section: Introductionmentioning
confidence: 99%
“…Pressure injuries can occur on various anatomical locations because of intense and/or prolonged pressure, or pressure in combination with shear and friction forces (Edsberg et al, 2016). Pressure injuries can have negative impacts on patients' physical, social, and psychological aspects of quality of life (Gorecki et al, 2009, Jackson et al, 2018, increase financial burden and hospital length of stay, and increase morbidity and mortality (Liu et al, 2019, Spetz et al, 2013, Theisen et al, 2012. A systematic review reported that costs related to the treatment of pressure injuries adds to the national annual budget from €121.44 million to €2.59 billion, with individual pressure injury treatment costs ranged from €15 to €69,472 in the USA, UK, the Netherlands, and Canada (currency was converted into Euros by the review authors) (Demarré et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Einrichtungen und das Gesundheitssystem vor finanzielle und strukturelle Herausforderungen. Für den Patienten selbst geht ein Dekubitus oftmals mit einem verlängerten Aufenthalt, Komplikationen, Schmerzen oder einer verringerten Lebensqualität einher, zumal die Entstehung eines Dekubitus zum Teil vermeidbar ist [5].…”
unclassified